2022
DOI: 10.1002/ajoc.202200012
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances Towards the Synthesis of Dihydrobenzofurans and Dihydroisobenzofurans

Abstract: The 2,3-dihydrobenzofuran heterocyclic systems are found in various biologically active natural and pharmaceutical products of biological relevance such as Phalarine, Rocaglamide, and Furaquinocin A. The interest in the study of 2,3-dihydrobenzofurans is constantly increasing because of their numerous biological properties such as anti-tumor, anticancer, anti-tubercular, and anti-malarial activities. Different methods have been established towards the synthesis of 2,3dihydrobenzofurans involved via intra-and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 120 publications
0
18
0
Order By: Relevance
“…Various natural products and synthetic medicines contain this component, which unlocks new potential for further synthetic applicability. 45 In Nov 2020, Sun and co-workers 46 developed a strategy for synthesizing sulfonyl-bearing DHB scaffolds via radical cascade annulation under visible-light irradiation. As shown in Scheme 25, the exploitation of 2-alkynylarylethers ( 25a , 0.2 mmol) and sodium sulfinates ( 25b , 0.4 mmol) in conjunction with metal photocatalyst Ir[(ppy) 2 (dtbbpy)]PF 6 (2 mol%), additive AcOH & water and solvent DMF under 30 W blue LED irradiation and N 2 atmosphere at room temperature for 24 h provided the intended product 25c with up to 78% yield.…”
Section: Ir-photocatalyzed Cascade Reactionmentioning
confidence: 99%
“…Various natural products and synthetic medicines contain this component, which unlocks new potential for further synthetic applicability. 45 In Nov 2020, Sun and co-workers 46 developed a strategy for synthesizing sulfonyl-bearing DHB scaffolds via radical cascade annulation under visible-light irradiation. As shown in Scheme 25, the exploitation of 2-alkynylarylethers ( 25a , 0.2 mmol) and sodium sulfinates ( 25b , 0.4 mmol) in conjunction with metal photocatalyst Ir[(ppy) 2 (dtbbpy)]PF 6 (2 mol%), additive AcOH & water and solvent DMF under 30 W blue LED irradiation and N 2 atmosphere at room temperature for 24 h provided the intended product 25c with up to 78% yield.…”
Section: Ir-photocatalyzed Cascade Reactionmentioning
confidence: 99%
“…Chiral 2,3-dihydrobenzofurans are ubiquitous and important ring structures embedded in some natural products and synthetic drugs with diverse bioactivities. Consequently, the synthesis of structurally diverse 2,3-dihydrobenzofuran compounds via a catalytic asymmetric manner has attracted tremendous attention from synthetic chemists [59,60] . In 2015, Lei et al reported a facile synthesis of racemic 2,3-dihydrobenzofurans via formal [4 + 1] cyclization of sulfonium ylides and in situ generated ortho-quinone methides (o-QMs) from O-silylated phenols [61] .…”
Section: Organocatalyzed Asymmetric [4 + 1] Cyclization Reactionsmentioning
confidence: 99%
“…Importantly, the 2,3-dihydrobenzofuran core is widely present in natural compounds and biologically active drugs . This class of products displays various biological activities, such as anti-HIV, antimalarial, anticancer, antinociceptive, anti-inflammatory, antifungal, and antibacterial activities. , …”
Section: Introductionmentioning
confidence: 99%